Assessment of Heavy Metals in the Water of Sahastradhara Hill Stream at Dehradun, India - Bharti, Pawan Kumar; Tyagi, Pawan Kumar; Singh, Vijender (International Journal of Environment, 2014)
A study on heavy metals assessment in the water of Sahastradhara hill-stream was conducted with different five sites at significant differences. The present paper deals with the water quality status of Sahastradhara stream by the assessment of heavy metals. Heavy Metals were found in fluctuated trend from first upstream to last downstream. The values of almost all Heavy Metals were found in increasing manner especially after the fourth sampling site. After the third sampling station, a solid waste dumping site was found. So, there may be a relation between heavy metals in stream water and solid waste dumping site. Concentrations of all Heavy Metals at fourth and fifth sampling site were found very high. DOI: http://dx.doi.org/10.3126/ije.v3i3.11076 International Journal of Environment Vol.3(3) 2014: 164-172